Pengaruh Penggunaan Coolant 30/70 Pre-Mixed Dan Coolant Predilute 33% Pada Sistem Pendingin Terhadap Temperatur Engine Toyota Avanza Tipe-E 1300 CC M/T - Suparno Suparno; Abd. Halim; Hariadi Hariadi; Didik Sutrisno (Politeknik Negeri Samarinda, 2020)
Cooling system has an important role in motor vehicles, because its function is to maintain the working temperature of the engine, so that the temperature does not exceed the threshold (over heating), due to the frequent causes of excessive heat due to the use of cooling water in the radiator. The research method used is an experimental method, where the aim is to determine the effect of coolant on engine temperature from the use of several types of coolant additives. The cooling water used is coolant 30/70 pre-mixed and coolant predilute 33%. This test is carried out at rounds of [600, 1500, 2000, 2500, 3000] RPM. The object of this research is the Toyota Avanza Type E 1300 CC M/T. From the results of research on engine temperature data with the use of coolant 30/70 Pre-mixed at various variations of engine speed obtained an average temperature of 94.13 OC. While the use of coolant predilute 33%, the average temperature in testing reaches 94.4 OC. Based on the description of the results of the test data that has been done, it was concluded that the use of coolant 30/70 pre-mixed and coolant predilute 33% has the same effect on the temperature of the Toyota Avanza Type-E 1300 CC M/T engine.